Identification of novel pQTL‐SNPs associated with lung adenocarcinoma risk: A multi‐stage study - Yutong Wu; Huiwen Xu; Liping Mao; Rongrong Zhao; Junfeng Chu; Lili Huang; Wendi Zhang; Yiran Liu; Qiong Chen; Xiaobo Tao; Siqi Li; Shenxuan Zhou; et al. (Cancer Medicine)
Abstract Background and Objective To explore the association between protein quantitative trait loci (pQTL‐SNPs) and the risk of LUAD. Methods “Blood +” high depth blood proteomics analysis was performed on plasma from female LUAD patients and female healthy controls, and combined with proteomics data from tumors and adjacent non‐tumor tissues of female LUAD patients to screen proteins uniformly expressed in plasma and tissues. pQTL‐SNPs were then screened through multiple databases and subjected to multilevel screening. The associations between selected pQTL‐SNPs and LUAD risk were evaluated by Female Lung Cancer Consortium in Asia GWAS (FLCCA GWAS). Enzyme linked immunosorbent assay (ELISA) is used to determine the levels of candidate protein. Results A total of 7 pQTL‐SNPs were significantly associated with altered LUAD risk (p < 0.05). Meanwhile, the expression of their corresponding target proteins were all decreased in both plasma and tumor tissues of LUAD cases, which may play a role of tumor suppressor proteins. After mutation of 3 pQTL‐SNPs (rs7683000, rs73224660, and rs2776937), the expression of corresponding target proteins BST1 and NRP1 decreased, and as potential tumor suppressor proteins, which may promote tumorigenesis and further increasing the risk of developing LUAD (OR >1, p < 0.05); while after mutation the other pQTL‐SNP rs62069916, the corresponding target protein APOH expression was increased, while as a potential tumor suppressor protein, which may inhibit tumorigenesis and further reduced the risk of developing LUAD (OR <1, p < 0.05). In addition, the expression of NRP1 and APOH were significant decreased in LUAD cell lines and validated in plasma of LUAD patients. Conclusion A total of 4 pQTL‐SNPs (rs7683000, rs73224660, rs2776937, and rs62069916) may associate with altered LUAD risk by regulating the expression of target proteins (BST1, NRP1, and APOH) after mutation.